2022
DOI: 10.3390/e24050620
|View full text |Cite
|
Sign up to set email alerts
|

Application of Coarse-Grained (CG) Models to Explore Conformational Pathway of Large-Scale Protein Machines

Abstract: Protein machines are clusters of protein assemblies that function in order to control the transfer of matter and energy in cells. For a specific protein machine, its working mechanisms are not only determined by the static crystal structures, but also related to the conformational transition dynamics and the corresponding energy profiles. With the rapid development of crystallographic techniques, the spatial scale of resolved structures is reaching up to thousands of residues, and the concomitant conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The structures modeled in this study all followed the workflow we reported previously [ 20 ]. First, the structures of the inactive, intermediate, and active states were extracted from corresponding experimental structures, which were as follows: β 2AR-inactive (PDB ID: 6EG8), β 2AR-intermediate (PDB ID: 6E67), β 2AR-active (PDB ID: 3SN6), GCGR-partially active (PDB ID: 5YQZ), GCGR-fully active (PDB ID: 6WPW), mGluR2-inactive (PDB ID: 7EPA), and mGluR2-fully active (PDB ID: 7E9G).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures modeled in this study all followed the workflow we reported previously [ 20 ]. First, the structures of the inactive, intermediate, and active states were extracted from corresponding experimental structures, which were as follows: β 2AR-inactive (PDB ID: 6EG8), β 2AR-intermediate (PDB ID: 6E67), β 2AR-active (PDB ID: 3SN6), GCGR-partially active (PDB ID: 5YQZ), GCGR-fully active (PDB ID: 6WPW), mGluR2-inactive (PDB ID: 7EPA), and mGluR2-fully active (PDB ID: 7E9G).…”
Section: Methodsmentioning
confidence: 99%
“…The idea of such coarse-graining has become a common, well-accepted, and powerful strategy [ 16 ]. Here, we investigated the activation process of GPCRs using a coarse-grained (CG) model [ 17 , 18 , 19 , 20 ], which has been proven to be very effective in investigating many biophysical systems such as ATPase [ 21 , 22 ], SARS-CoV-2 spike [ 23 , 24 ], and GPCRs [ 25 , 26 , 27 ]. The CG strategies for a description of the functional properties focused on improving the electrostatic features of the model [ 17 ] and were refined for the treatment of membrane proteins [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, the treatment of electrostatic effects in this CG model is a key factor in clearly explaining the energetics in many complicated and large biological systems [ 19 , 27 , 28 ]. It is computed as a sum of the change in free energy associated with charge–charge interactions between ionizable side chains.…”
Section: Methodsmentioning
confidence: 99%